The performance analysis of a service deployment system based on the centralized storage - Dong, Z.X. (Journal of Digital Information Management, 2011)
Because of its data centralized management characteristic, which conveniently realize resources sharing and the data fast clone, the service deployment technology based on the centralized storage can achieve fast deployment for the system service through the network boot methed or the method of downloading disk image from the remote storage server. However, for the data centralism the I/O load is also congested on the storage server, which creates the drop of the overall system performance and the reducing of the service quality. So we need to test and analyze its performance factors, which provide the clue for the solution of the performance bottleneck. In this paper, we use the SonD deployment system, which is based on the centralized storage, as the analysis prototype to carry on the analysis to the client boot process, evaluate its performance influence factors such as the memory size of storage server, data distribution on the storage server through the real or simulated method, and give suggestion of the performance optimized.
Keywords: Centralized Storage; Performance Analysis; Service Deployment